European Union commitments and policies towards indigenous people’s human rights: A case study of the Sámi people and the EU’s Critical Raw Materials Act - Emma Hartshaw (Australian and New Zealand Journal of European Studies)
This essay examines the European Union’s commitments and policies towards indigenous people’s human rights, the Sámi people and the EU’s Critical Raw Materials Act (CRMA). For the Sámi, the Act actively violates the human rights they are entitled to. For the EU, the Act highlights internal institutional disputes and the impact that fast-tracking laws has upon indigenous human rights. This essay outlines an overview of the EU’s commitments to indigenous people’s human rights, a discussion of both EU Member States’ and European Economic Area states’ regional Sámi human rights, discourse surrounding the EU policies that affect Sámi and their human rights, as well as critically analysing the CRMA and its impact on Sámi people. The essay concludes with the argument that the EU is actively violating the human rights of indigenous peoples that it promises to protect and promote.